Novas estratégias da produção imobiliária na Grande Vitória : um estudo sobre as recentes transformações do espaço urbano da Serra-ES - Gonçalves, Thalismar Matias (2010)
It discusses the relation between the real estate market and the production of the urban space from the recent transformations which has occurred in Serra, located in the Metropolitan Region of Grande Vitória (RMGV). Historically, the real estate activity has been manifested in Grande Vitória through the vertical residential production in Vitória and in Vila Velha. This process is recent in Serra and has been materialized in gated communities (houses or buildings). The analyzed period starts in 2000, when it was released the first gated community, and finishes in 2008. The main goal of this research was identifying particular strategies of the real estate capital in Serra. From the perspective that considers the real estate production as part of the new contents of the contemporary urbanization. The data was collected through primary sources, such as interviews with correctors and businessmen and, as secondary sources, research in the companies’ websites, newspapers and catalogues. During the research, they were identified two periods about the real estate dynamics in Serra. Between 2000 and the beginning of 2006, the real estate market was characterized by the slow rhythm, by the predominance of gated community of houses and by the exclusive acting of local companies. The second period occurred between the end of 2006 and 2008, when the real estate production reached consolidation as an agent who builds the urban space in the city. Serra came to be the privileged locus of the real estate investments in Grande Vitória as they have been brought great incorporating companies in Espírito Santo, seated in other states as Rio de Janeiro and São Paulo. In this context, they were released thousands of habitations in gate communities of houses e buildings, towards several classes. The results show that the real estate production in Serra raises itself on the combination of strategies attached to the appropriation of “rare stuff” insert in the contemporary urban space. There is a real estate product (gate community) which searches for becoming different from any others by the offer of options which became “rare stuff” in the city, such as security, nature, fun and social relations. On the other hand, the incorporating companies seek for appropriating some specific central locations, historically produced, exactly what happens around Laranjeiras, an important sub-center of RMGV.